2021
DOI: 10.1042/bsr20211451
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a glycolysis-related lncRNA prognostic signature for clear cell renal cell carcinoma

Abstract: Background: This study investigated the independent prognostic value of glycolysis-related long noncoding (lnc)RNAs in clear cell renal cell carcinoma (ccRCC). Methods: A coexpression analysis of glycolysis-related mRNAs–lncRNAs in ccRCC from The Cancer Genome Atlas was carried out. Clinical samples were randomly divided into training and validation sets. Univariate Cox regression and least absolute shrinkage and selection operator regression analyses were performed to establish a glycolysis risk model with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…By using expression analysis and correlation analysis, the most potential upregulated lncRNAs AC026401.3 was identified ( Figure 4D , 4E ). Glycolysis based AC026401.3 have important value in survival prediction of renal cell carcinoma patients [ 23 ], but their specific roles in tumors are unclear and deserve further exploration [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using expression analysis and correlation analysis, the most potential upregulated lncRNAs AC026401.3 was identified ( Figure 4D , 4E ). Glycolysis based AC026401.3 have important value in survival prediction of renal cell carcinoma patients [ 23 ], but their specific roles in tumors are unclear and deserve further exploration [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs could also be used to predict the prognosis of diseases. Ma et al found that the 7 identified glycolysis-related lncRNAs constitute a lncRNA signature with prognostic value for clear cell renal cell carcinoma and provide potential therapeutic targets for the treatment of clear cell renal cell carcinoma patients [ 38 ]. The ROC curve results showed that lncRNA NEAT1_1 in peripheral blood of STB patients had satisfactory sensitivity, specificity, and AUC in predicting the outcome of STB, which suggested that RNA in peripheral blood might be used to predict prognosis of STB.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al identified an m6A-related lncRNA signature for predicting the prognosis of RCC, with an AUC value of 0.80 ( Yu et al, 2021 ). Ma et al identified a glycolysis-related lncRNA prognostic signature for RCC and the AUC value was 0.82 ( Ma et al, 2021 ). Dong et al identified a redox-related lncRNA signature of RCC and the AUC value was 0.82 ( Qi-Dong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported several prognostic models for RCC. However, the Area Under Curve (AUC) values were all less than 0.83 (Qi-Dong et al, 2020;Ma et al, 2021;Sun et al, 2021;Yu et al, 2021). Therefore, a more efficient model is urgently needed for predicting the prognosis of RCC.…”
Section: Introductionmentioning
confidence: 99%